Write or wrong; An analysis of Thai children’s writing samples - Kunkudatharn, N (2021)
Thai is an alphasyllabic orthography and a tonal language with a non-linear arrangement of written vowels. The current study aimed to explore children’s Thai writing development through an error analysis of existing writing samples. An additional aim investigated the associations between the children’s Home Language and Literacy Environment (HLLE) and errors from the writing samples. The sample consisted of 31 Thai- English bilingual and multilingual children between 8-11 years of age from international schools across Thailand. The children’s writing samples were examined on factors that make up the translation processes of writing (transcription and text generation) including measures of word count, number of ideas and spelling errors. A spelling coding scheme was created to capture the different error types. Thai is a scriptio continua, which means that it has no spaces between words, so space knowledge is also important in Thai knowledge development.